Digital medicine : bioethical assessment of challenges and opportunities - Grebenshchikova, Elena (Array, 2019)
The digital health industry is developing rapidly: many new subjects are involved in the field of medicine; new opportunities for distant medical services, diagnostics, monitoring of patients’ health, and conducting medical research are emerging; electronic medical documentation is being developed, global medical information databases are being formed, etc. At the same time, the format of doctor-patient relationships is being transformed and new issues and challenges arise that require ethical evaluation. I identified three areas of digital medicine and analyzed issues of confidentiality, informed consent, autonomy and equity in each case. The impact of digital health technologies on the ethical contexts of medicine is uneven: telemedicine possesses the smallest revolutionary potential, which changes the mechanisms of doctor-patient interaction and actualizes issues of cultural differences. mHealth technologies significantly affect patient autonomy and change ways of sharing medical information. Artificial Intelligence (AI) is diverse in medicine, it can depersonalize relationships in medicine, radically change ideas about the role of the doctor and patient, lead to a radical restructuring of the medical care system in the center of which will be the new model of patient interaction with automated medical agents and systems.